Preliminary Development and Assessment of a Multiplex Assay for Human Papillomavirus Antibody Detection Using Commercial L1 Proteins - Arash Aslanabadi; Maryam Karimi; Laura Powell; Lisa Schumaker; Ashley Shutt; Mahsa Hojabri; Rahim Abbasi; Søren M. Bentzen; Kevin J. Cullen; Trevor A. Crowell; Rebecca G. Nowak; Mohammad M. Sajadi (Journal of Clinical Laboratory Analysis, 2026)
ABSTRACT Background Human papillomavirus (HPV)‐associated cancers are preventable with vaccination. Serologic assays monitor antibody responses, but their complexity and cost pose limitations when evaluating population level immunity. We developed an L1‐based assay for the detection of multiple type‐specific HPV antibodies. Methods The Luminex‐based assay used recombinant L1 proteins from seven HPVs (HPV‐6/11/16/18/35/45/58) for the detection of type‐specific immunoglobulin (Ig)G and IgA. Cutoffs were established using plasma from infants and children. The assay was optimized and qualified using a sample set from a blinded proficiency panel developed at the Frederick National Laboratory for Cancer Research. Results Sensitivity and specificity for anti‐HPV‐6/11/16/18/58 IgG were 100% at the Mean + 3 standard deviation [SD] and Mean + 5 SD thresholds. Sensitivity for HPV‐45 was 100% and 92.9% at the +3 SD and +5 SD thresholds, respectively. IgA detection showed moderate positivity among vaccinated individuals, with peak estimates of 96.4% (HPV‐11) and 85.7% (HPV‐58) at the +3 SD threshold. IgA was correlated with IgG (Spearman's ρ = 0.74). The L1‐assay differentiated high, intermediate, low, and negative response groups from the blinded samples for all HPV genotypes ( p < 0.0001). Conclusion The L1‐binding assay has the potential to be a scalable option for high‐throughput detection of broad‐spectrum HPV immunoglobulins, but further standardization and validation are needed.